„Wolność kontrolowana” — o (nie)zależności tłumacza. Uwagi do polskiego przekładu powieści Petry Hůlovej Umělohmotný třípokoj - Żygadło‑Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2015)
„Controlled freedom” — about the (in)dependence of a translator. A few comments about the Polish translation of Petra Hůlová’s Umělohmotný třípokoj In 2002 in the Czech Republic a very interesting phenomenon occured — an unknown young woman named Petra Hůlová published a book, which caused the biggest literary stir of recent years. The writer’s debut Paměť mojí babičce received the Magnesia Litera Award in the Objev roku (Discovery of the Year) category and won the Lidove noviny’s poll as Kniha roku (Book of the Year). The prose of Umělohmotný třípokoj won the Jiry Orten Award. In 2008, Hulova was awarded with the Josef Škvorecký Award for the novel Stanice Tajga. In every book the writer seems different, which does not mean that she has no individual style. She is undoubtedly the most award‑winning young author today. She captured readers’ attention with the language used, which is a mixture of colloquial Czech and surprising similes. Quite unique is also the bravery of her storytelling. The book we are interested in, Umělohmotný třípokoj, is the fourth novel by the young writer. The Polish translator Julia Różewicz was awarded for the “New face” category of the literary magazine Literatura na Świecie for her translation of the Petra Hulova’s book (in Polish: Plastikowe M3, czyli czeska pornografia, Afera 2013). The goal of this study is to analyze the Czech author’s specific language and to later confront it with the language chosen for its “Czech mutation” by the translator, Julia Różewicz. Key words: Czech literature, translation, language, interpretation, freedom